Media content about vaccines in the United States and Canada, 2012–2014: An analysis using data from the Vaccine Sentimeter. Issue 50 (7th December 2016) - Powell, Guido Antonio; Zinszer, Kate; Verma, Aman; Bahk, Chi; Madoff, Lawrence; Brownstein, John; Buckeridge, David
Highlights: We analyzed online vaccine discussion from the Vaccine Sentimeter media monitor. Our regional focus identified patterns of sentiment and themes in the US and Canada. More negative sentiment was found in media discussing events in Vermont's (18%). Mentions of religious beliefs in coverage of measles outbreaks varied by region. Insights from such regional analyses can inform and guide future public health action. Abstract: Background: A system for monitoring vaccine-related media content was previously developed and studied from an international perspective. This monitoring approach could also have value at a regional level, but it has yet to be evaluated at this scale. We examined regional patterns of vaccine-related media topics and sentiment in the US and Canada. Methods: We extracted vaccine-relevant US and Canadian online media reports between June 2012 and October 2014 from the Vaccine Sentimeter, a HealthMap-based automated media monitoring system for news aggregators and blogs. We analyzed regional distributions of reports about vaccines, categories (i.e., topics), sentiment, and measles outbreaks. Findings: The Vaccine Sentimeter captured 10, 715 reports during the study period. Negative sentiment was highest in reports about vaccine safety (47%), Hepatitis B (19%), and Vermont (18%). Analyses of measles outbreaks revealed geographical variation in media content. For example, religious beliefs were mentioned in 27% of measles reports in Texas and 22% of British Columbia reports, but there were no references to religion in media on measles from California. Interpretations: A regional analysis of online sentiment towards vaccine can provide insights that may give US and Canadian public health practitioners a deeper understanding of media influences on vaccine choices in their regions and consequently lead to more effective public health action.